SAT0338 CONTRAST-ENHANCED ULTRASONOGRAPHY IN THE EVALUATION OF MYOSITIS. (2nd June 2020) - Pipitone, N.; Macchioni, P.; Bajocchi, G.; Salvarani, C.
Abstract : Background: contrast-enhanced ultrasonography (CEUS) has been proposed as a tool to assess myositis, but data in the literature are still scarce (Radiologe 2018;58:579). Objectives: to evaluate CEUS as a tool to assess myositis patients and its accuracy in differentiating myositis from common mimickers. Methods: 16 patients with myositis (4 polymyositis, 6 dermatomyositis, 2 immune-mediated necrotizing myopathy, 1 inclusion body myositis, 2 overlaps Sjøgren's syndrome - myositis and 1 Enterovirus-reactive myositis) and 4 controls (2 peripheral neuropathy, 1 limb girdle muscle dystrophy, and 1 metabolic myopathy) underwent after rest CEUS (Esaote MyLab, linear probe 13-5 MHz, Sonovue®) at a room temperature of 20° of the vastus lateralis and medialis muscles. CEUS was performed by 2 ultrasonographists with an expertise in muscle US blinded to the clinical data of the patients. CEUS muscle signal was expressed on a 0-4 scale as described in J Rheumatol 2001; 28:1271 per each muscle group and the global score was divided by four. Creatine kinase (CK), manual muscle test (MTT) and MRI of the thigh muscles were performed within maximum one month from the CEUS. MMT was expressed using the 0-5 Medical Research Council scale; intermediate points were converted into decimals as detailed in Kendall FP et al, Muscle Testing & Function: Testing and Function with Posture and Pain. 5th ed., Lippincott Williams & Wilkins, 2005. MRI of the thigh muscles was considered positive if it showed muscle edema. Myositis was defined active if CK was raised above the reference range and/or MMT showed progressive worsening. Results were expressed as median (range). Between-group comparison was performed with Mann-Whitney test. Statistical analysis was performed with SPSS version 20. The study was approved by the Ethics Committee and all patients provided their written consent. Results: Median (range) age was 38 (69) years in the myositis and 41 (45) years in the control group (p=0.89). Disease duration in the myositis group was 60 (334) months. CEUS muscle score was 0.5 (3) in the myositis group and 2 (3) in the control group (p=0.99). In the myositis group, CEUS score did not differ between treated and untreated patients (p=0.84). CK values were 361 (6442) in the myositis group and 363 (799) in the control group (p=0.68). MMT was significantly lower in the myositis group [4.33 (2)] than in the control group [4.94 (0)] (p=0.038). CEUS was 77% (47-05 95% confidence interval) sensitive and 67% (9-99% 95% confidence interval) specific for a diagnosis of myositis. CEUS was positive in 10/13 patients and negative in 3/13 with active myositis, while was negative in 2/3 patients and positive in 1/3 with inactive myositis. Statistically, CEUS did not discriminate between active and inactive myositis (Fisher's exact test p= 0.21). All controls had a positive CEUS. No association was found between MRI edema and a positive CEUS (intraclass correlation coefficient p=0.5). No correlation was found between CEUS score, on the one hand, and CK levels or MMT, on the other (Spearman's rho p>0.05). Conclusion: CEUS has moderate sensitivity for a diagnosis of myositis, but does not discriminate between myositis and some of its common mimickers. Larger studies are required to better evaluate the role of CEUS in patients with myositis. Disclosure of Interests: Nicolo Pipitone Consultant of: Received royalties from Uptodate.com Investigator for the gevokizumab in myositis Servier study (2014), the sirukumab in GCA GSK study (2016), PI for the ToReMy AIFA funded (2017) study and for the FOREUM funded (2018) GCA study, Speakers bureau: Guest speaker at UCB-sponsored meetings: (Immunology Summits, Prague, 2012, 2013 & 2014, MACRO Meet the expert at the ACademy of RheumatOlogy, Bologna 13 - 14 April 2012, GRAPPA Workshop, Milan 29 January 2016 and Rome 30 November 2017), Fininvest (Catania 2016), Aim Group (Reggio Emilia 2018), I&C (Cologna, 2018), Alfa-Wassermann sponsored meeting (Rhewind, Bologna, February 2016 and 2019), Pierluigi Macchioni: None declared, Gianluigi Bajocchi: None declared, Carlo Salvarani Grant/research support from: consulting and investigator fees from Abbvie, Pfizer, MSD, Roche, Celgene, Novartis, Consultant of: consulting and investigator fees from Abbvie, Pfizer, MSD, Roche, Celgene, Novartis